2014
DOI: 10.2147/dddt.s68818
|View full text |Cite
|
Sign up to set email alerts
|

Ferulago angulata activates intrinsic pathway of apoptosis in MCF-7 cells associated with G1 cell cycle arrest via involvement of p21/p27

Abstract: Ferulago angulata is a medicinal plant that is traditionally known for its anti-inflammatory and antiulcer properties. The present study was aimed to evaluate its anticancer activity and the possible mechanism of action using MCF-7 as an in vitro model. F. angulata leaf extracts were prepared using solvents in the order of increasing polarity. As determined by MTT assay, F. angulata leaves hexane extract (FALHE) revealed the strongest cytotoxicity against MCF-7 cells with the half maximal inhibitory concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Overexpression of cyclin D1 is known to correlate with the risk of tumor progression (29). The p21 and p27 genes have recently been discovered to be important cyclin-dependent kinase inhibitors (CDKIs) and regulate the cell cycle as well as DNA replication and repair (30). Our results found that the expression of cyclin D1 was decreased whereas levels of p21 and p27 were upregulated.…”
Section: Discussionmentioning
confidence: 60%
“…Overexpression of cyclin D1 is known to correlate with the risk of tumor progression (29). The p21 and p27 genes have recently been discovered to be important cyclin-dependent kinase inhibitors (CDKIs) and regulate the cell cycle as well as DNA replication and repair (30). Our results found that the expression of cyclin D1 was decreased whereas levels of p21 and p27 were upregulated.…”
Section: Discussionmentioning
confidence: 60%
“…In our previous investigation, F . angulata leaf hexane extract (FALHE) was found to induce apoptosis in MCF7 cells via a mitochondrial-dependent pathway and cell cycle arrest [ 15 ]. Thus, the aims of the present study were to examine the in vivo chemopreventive effect of FALHE against LA7-induced breast tumors in rats and to investigate polycerasoidin as a cytotoxic compound and its underlying mechanism of action using a bioassay-guided approach.…”
Section: Introductionmentioning
confidence: 99%
“…This study explained the potential use of red Pistacia vera hull as chemopreventive drug, as it can be exploited as a new lead compound for prodrug therapy. Since MCF7 is an estrogen-receptor negative human breast cancer, it's good for potential future examination of our extract and its active compound in another estrogen receptor-responsive cell line like MDA-231 [23]. Also as extracts of plants may activate the immune system of the hosts and kill cancer cells, one can consider testing the concentrations of various cytokines, tumor necrosis factor, etc.…”
Section: Discussionmentioning
confidence: 99%